Assessing Lecturers' perceived motivational strategies in Nigerian private universities During COVID-19 lockdown: evidence from Al-Hikmah University / Yusuf Suleiman ... [et al.] - Jemeelah, Olajide Olaide; Suleiman, Yusuf; Ishola, Mustapha Adam; Sekinat, Katibi Olatinuke (2021)
The novel covid-19 pandemic led to lockdown measures, part of which disrupted academic activities in Nigerian universities. It is on this premise that this study examined lecturers‟ perceived motivational strategies in Nigerian private universities during covid-19 lockdown with evidence from Al-Hikmah University. Three research questions were formulated to guide the study. The research design adopted was a descriptive type of survey. The population consists of all academic staff in Al-Hikmah University. Stratified and simple random sampling techniques were used to select 108 respondents across the seven faculties in the university. An instrument titled "Lecturers‟ Perceived Motivational Strategies Questionnaire (LPMSQ)" was adapted to elicit relevant data. The data collected were analysed using a descriptive method. Findings from the study showed the motivational strategies that were used to motivate lecturers during the lockdown. The strategies include promotion, salary and working condition. The findings also revealed challenges that were associated with the motivational strategies in the university. The challenges are paucity of fund and lack of support from external bodies. Based on the findings, the study recommended that salaries and allowances of lecturers should be sustained. Also, lecturers should be promoted as at when it is due. This is with a view to reducing the phenomenon of brain drain in the university.